Separation of phenylsuccinic acid enantiomers using biphasic chiral recognition high‐speed countercurrent chromatography. Issue 14 (5th June 2014) - Sun, Genlin; Tang, Kewen; Zhang, Panliang; Yang, Weijun; Sui, Guoqing
<x xml:space="preserve">Abstract</x> High‐speed countercurrent chromatography (HSCCC) combined with biphasic chiral recognition was successfully applied to the resolution of phenylsuccinic acid enantiomers. d‐Isobutyl tartrate and hydroxypropyl‐β‐cyclodextrin were employed as lipophilic and hydrophilic selectors dissolved in the organic stationary phase and aqueous mobile phase, respectively. The two‐phase solvent system was made up of n‐hexane/methyl tert‐butyl ether/water (0.5:1.5:2, v/v/v). Impacts of the type and concentration of chiral selectors, the pH value of the aqueous phase solution as well as the temperature on the separation efficiency were investigated. By means of preparative HSCCC, pure enantiomer was obtained by separating 810 mg of racemate with a purity >99.5% and a recovery rate between 82 and 85%. The experimental results indicate that biphasic recognition HSCCC provide a promising means for efficient separation of racemates.